The Role of the Bogor Police Traffic Dikmas in Reducing Motorcycle Traffic Violations - Rifqy Pratama (Advances in Police Science Research Journal, 2021)
This research is motivated because traffic violations committed by motorcycle riders in the jurisdiction of the Bogor Police have a fairly high number. This problem occurs because of the lack of knowledge, discipline, and public awareness in orderly traffic, especially regarding problems that often occur such as the use of helmets, and the completeness of driving documents. So that the role of Dikmas then as a form of pre-emptive and preventive in reducing traffic violations is needed. The approach used in this research is a qualitative approach and this type of research is field research. The focus of this research is the role of Traffic Dikmas in reducing traffic violations committed by motorcyclists in the jurisdiction of the Bogor Police. The sources of information in this study were the ranks of the Bogor Police Satlantas and users of two-wheeled motorized vehicles. Data collection techniques were carried out by means of interviews, observations, and document observations. The results showed that the role of Traffic Dikmas in reducing traffic violations by two-wheeled motorized vehicles in the jurisdiction of the Bogor Police was less than optimal. This happens because of several things, namely from the community itself, Dikmas activities that have not been carried out according to the rengiat, the lack of personnel, and other factors that make the implementation of Dikmas Then not run effectively. As a suggestion that the role of the Traffic Dikmas can reduce traffic violations by motorized vehicles in the area of ​​the Bogor Police, including making an activity plan according to the situation and conditions in the field, submitting personnel for Dikjur and training related to Traffic Dikmas, as well as collaboration with the Sector Police ranks to help deliver the message of Kamseltibcarlantas.